DESIGN DEVELOPMENT AND FABRICATION OF NOVEL PLATFORM FOR ORODISPERSIBL TABLETS - Gharge, Vikram; Sharma, Peeyush; Bhandari, Anil; Gonjari, Indrajeet (Asian Journal of Pharmaceutical Research and Development, 2013)
Evolution of existing drug molecules from a conventional form to novel delivery system can significantly improve its performances in term of patient compliance, safety, and efficacy. These days drug delivery companies are engaged in the development of multiple platform technologies to get competitive advantage extend patent life and increase market share of their products. In the present study an attempt has been made to develop a platform for orodispersible tablet. Fluid bed granulation technique was utilized to prepare granules using various concentrations of fillers, superdisintegrants, wetting agents, solubilizer and sweetener. The prepared blend was evaluated for pre compression parameters such as granule size, loss on drying, bulk density, compressibility index and angle of repose. The prepared batches of tablets was evaluated for the weight variation, mechanical strength, attrition resistance test, friability, fracture resistance test,crusing strength and diameter, disintegration test water absorption test and wetting time. Among the formulation contain mannitol as filler and Crospovidone 15mg/tab as superdisintegrants with low substituted hydroxypropyl cellulose LH 11 4 mg/tablet and sucralose 3 mg/tab as sweetener show best wetting and disintegration time with minimal mechanical properties.